THE APLICATION OF ISLAMIC LAW IN INDONESIA: The Case Study in Aceh (JOURNAL OF INDONESIAN ISLAM, 2007)
This article provides an historical account of the implementation of Islamic law in Aceh and how the issue of Islamic law has been debated. The study will give more emphasis on the dynamics of the implementation of Islamic law, its historical development, typologies of Islamic law, leaders’ opinions regarding this issue, and the governments’ responses. This study argues that Islamic law in Aceh has been misinterpreted merely as h{udu>d law. In addition, it argues that the provincial government tends to put heavy emphasis on symbolic religious issues (such as the Islamic dress code and the usage of Arabic signs and letterheads), rather than the substance of Islamic law such as justice and prosperity for all. Finally, the study has made evident that implementing Islamic law is never a good method of attempting to resolve conflict. There is no need to establish Islamic law formally through the political process because, when politics enters in religious arena, it carries with it many interests.